Antioxidative and cytotoxic activities of crude and isolated compounds of Polyalthia lateriflora (Bl.) King - Obaid, Ahmed Kareem; Syed Abdul Azziz, Saripah Salbiah; Mhd Bakri, Yuhanis; Nafiah, Mohd Azlan; Awang, Khalijah; Abdulla Aowda, Saadon; Mohd Hassan, Norazian; Hashim, Yumi Zuhanis Has-Yun; Abdullah, Fauziah (PharmaInfo Publications, 2018)
This study aimed to isolate compounds from Polyalthia lateriflora (Bl.) King stem bark, and to test the crude extracts and the isolated compounds for their antioxidant and cytotoxic activities. Three different solvents were used to prepare the crude extracts; hexane, dichloromethane (DCM) and methanol. Phytochemical investigation of the crude extracts has led to the isolation of four oxoaporphine alkaloids (O-methylmoschatoline, atherospermidine, lysicamine, and liriodenine) and two steroids (stigmasterol and lupeol). The chemical structure of the compounds was elucidated using 1H-NMR, 13C-NMR, 2D-NMR, and mass spectral analysis. All the crude extracts and isolated compounds were tested for their in vitro DPPH radicals scavenging activity and cytotoxicity against MCF-7 breast cancer cells. Methanol extract showed the strongest antioxidant activity with percentage inhibition at 500μg/mL of 89.52±1.81 (IC50, 128.22± 6.73 μg/ml) in comparison with DCM (32.45±8.56), atherospermidine (20.17±9.74) and liriodenine (10.73±0.45), while other extracts were inactive. All the isolated compounds showed cytotoxic against MCF-7 cells, at IC50 values in the range of 42-89 μg/ml. Based on thorough literature review, all compounds identified in this study were isolated for the first time from this plant. In particular, lupeol is reported for the first time in the genus Polyalthia and possessed the most potent cytotoxic effect compared to other isolated compounds.